TIRES FOR AGRICULTURAL MACHINERY (Perner's Contacts, 2016)
The article discusses about the tires that are used in agriculture machinery. The article discussed specifics of tires used in agriculture compared to tires for road vehicles. At the same time briefly analyzes the problem of wheeled and tracked tractor chassis of agriculture machinery
Keywords: agriculture machinery; tire; trackor